Analisis Pelaksanaan Program Adhyaksa Peduli Stunting Di Gampong Peuniti Kecamatan Baitturahman Kota Banda Aceh - Akbar, Aulia (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2025)
This study analyzes the implementation of the Adhyaksa Peduli Stunting Program in Gampong Peuniti, Baitturahman Sub-district, Banda Aceh City. The program aims to reduce stunting rates through supplementary feeding, health monitoring, and nutrition education for families with stunted children. Using a qualitative approach, data were collected through interviews, observation, and documentation. The findings indicate that the program was implemented in several stages, including data validation, coordination meetings, target determination, and program execution involving counseling, education, growth monitoring, and aid distribution. Over six months, the program significantly improved children's weight and reduced the number of stunted children from 45 to 13. The success of the program was influenced by cross-sector collaboration, service accessibility, and community involvement. These results are expected to provide valuable insights for future stunting prevention efforts.